Inequalities in physical comorbidity: a longitudinal comparative cohort study of people with severe mental illness in the UK. Issue 12 (15th December 2015) - Reilly, Siobhan; Olier, Ivan; Planner, Claire; Doran, Tim; Reeves, David; Ashcroft, Darren M; Gask, Linda; Kontopantelis, Evangelos
Abstract : Objectives: Little is known about the prevalence of comorbidity rates in people with severe mental illness (SMI) in UK primary care. We calculated the prevalence of SMI by UK country, English region and deprivation quintile, antipsychotic and antidepressant medication prescription rates for people with SMI, and prevalence rates of common comorbidities in people with SMI compared with people without SMI. Design: Retrospective cohort study from 2000 to 2012. Setting: 627 general practices contributing to the Clinical Practice Research Datalink, a UK primary care database. Participants: Each identified case (346 551) was matched for age, sex and general practice with 5 randomly selected control cases (1 732 755) with no diagnosis of SMI in each yearly time point. Outcome measures: Prevalence rates were calculated for 16 conditions. Results: SMI rates were highest in Scotland and in more deprived areas. Rates increased in England, Wales and Northern Ireland over time, with the largest increase in Northern Ireland (0.48% in 2000/2001 to 0.69% in 2011/2012). Annual prevalence rates of all conditions were higher in people with SMI compared with those without SMI. The discrepancy between the prevalence of those with and without SMI increased over time for most conditions. A greater increase in the mean number of additional conditions was observed in the SMI population over the study period (0.6 in 2000/2001 to 1.0 in 2011/2012) compared with those without SMI (0.5 in 2000/2001 to 0.6 in 2011/2012). For both groups, most conditions were more prevalent in more deprived areas, whereas for the SMI group conditions such as hypothyroidism, chronic kidney disease and cancer were more prevalent in more affluent areas. Conclusions: Our findings highlight the health inequalities faced by people with SMI. The provision of appropriate timely health prevention, promotion and monitoring activities to reduce these health inequalities are needed, especially in deprived areas.